Sistem Pendukung Keputusan Pemilihan Smartphone Terbaik Menggunakan Metode Copras (Complex Proportional Assessment) - Riska Silvia; Sriwinar; Hannan Asrawi (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
The rapid development of the smartphone industry has resulted in a wide variety of products with different specifications and prices. This condition often makes consumers confused when determining the best smartphone that suits their needs. Therefore, a decision support system is needed to assist users in selecting smartphones objectively based on several technical criteria. This study aims to develop a Decision Support System (DSS) for selecting the best smartphone in the price range of IDR 3–5 million using the Complex Proportional Assessment (COPRAS) method. The research evaluates several smartphone alternatives based on twelve criteria consisting of ten benefit criteria and two cost criteria. The COPRAS method processes the data through normalization, weighting, and utility value calculation to determine the ranking of each alternative. The results of the study show that the proposed system is capable of providing objective recommendations based on the utility value of each smartphone alternative. The system can assist users in making rational and data-driven decisions when selecting smartphones. In addition, the developed model can also be applied to other product selection problems involving multiple criteria.